Coordinated control of MMC‐HVDC system with offshore wind farm for providing emulated inertia support. Issue 5 (21st February 2020) - Zeng, Xueyang; Liu, Tianqi; Wang, Shunliang; Dong, Yuqing; Li, Baohong; Chen, Zhe
Abstract : With the continuous increase of renewable energy generation and high voltage direct current (HVDC) power transmission, the system inertia is declining, thus resulting in greater risks of frequency instability. To solve this issue, a dc‐link inertia control is firstly proposed for a point‐to‐point modular multilevel converter based HVDC (MMC‐HVDC) link, which enables the MMC‐HVDC system to provide emulated inertia support by employing the electrostatic energy stored in the dc capacitors. Moreover, in order to maintain reasonable submodule capacitor size as well as provide more emulated inertia support, a virtual capacitor control for MMC‐HVDC connected an offshore wind farm (OWF) is proposed. With the virtual capacitor control, the OWF is able to provide a large capacity virtual capacitor in dc side of MMC‐HVDC link and supply desired emulated inertia support for onshore power system by utilising the offshore wind turbines' rotor rotational kinetic energy. Furthermore, a procedure for selecting the appropriate virtual capacitor control parameters is proposed. Finally, the performance of the proposed coordinated control is researched in PSCAD/EMTDC, and the simulation results show that the onshore power system inertia is effectively improved with the coordinated control.